“Fördelen är att jag kan återhämta mig” - En kvalitativ studie om upplevelser av arbetstidsförkortning och dess relation till work-life balance - Neij,Julia; Mörk,Jenny (2025)
The thesis describes and analyzes individuals' experiences of reduced working hours with retained salary, as well as how this could potentially enable an improved work-life balance. It also investigates how participants experienced pros and cons with reduced working hours. The topic is relevant due to the ongoing societal debate about whether the current 40-hour workweek in Sweden should be reconsidered. The thesis adopts a hermeneutic approach, conducting qualitative interviews that have been interpreted and shaped the results, which are analyzed using theory. The theories focus on the different conditions that individuals and workplaces have that affect work-life balance, as well as how recovery and well-being can be achieved in working life. The results show that participants experience increased well-being and recovery, and consequently, a better work-life balance with the introduction of reduced working hours. Participants report feeling less stressed, having more time for recovery, and being better able to distance themselves from work during their free time. The results are limited by the fact that only four interviews were conducted but still confirm much of what previous research has shown. For future research, it might be interesting to focus on a specific target group or professional category. It could also be relevant to examine how third parties, such as care recipients, are affected by staff working reduced hours.
Keywords: Work-life balance; reduced working hours; recovery; sustainable working life